2022
DOI: 10.1073/pnas.2201275119
|View full text |Cite
|
Sign up to set email alerts
|

Sensory error drives fine motor adjustment

Abstract: Fine audiovocal control is a hallmark of human speech production and depends on precisely coordinated muscle activity guided by sensory feedback. Little is known about shared audiovocal mechanisms between humans and other mammals. We hypothesized that real-time audiovocal control in bat echolocation uses the same computational principles as human speech. To test the prediction of this hypothesis, we applied state feedback control (SFC) theory to the analysis of call frequency adjustments in the echolocating ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…They not only dynamically adjust the structure of echolocation signals to ongoing navigation and foraging tasks 37 , 38 , 39 but also rapidly modify signal features to cope with interfering sounds. 40 , 41 , 42 , 43 , 44 By contrast, little is known regarding the ability to adaptively adjust signal parameters at a longer timescale, which is relevant to long-term learning. 45 , 46 We suggest that the slow vocal adaptation to auditory masking in H .…”
Section: Resultsmentioning
confidence: 99%
“…They not only dynamically adjust the structure of echolocation signals to ongoing navigation and foraging tasks 37 , 38 , 39 but also rapidly modify signal features to cope with interfering sounds. 40 , 41 , 42 , 43 , 44 By contrast, little is known regarding the ability to adaptively adjust signal parameters at a longer timescale, which is relevant to long-term learning. 45 , 46 We suggest that the slow vocal adaptation to auditory masking in H .…”
Section: Resultsmentioning
confidence: 99%
“…transported in a moving pendulum setup (Figure 3, bottom panels). In a detailed study with the same playback setup on another Hipposiderid bat, H. armiger, we have shown that online vocal frequency adjustments by H. armiger are driven by sensory prediction errors, but not by DSC or by jamming avoidance response (Wang et al, 2022). Thus, below we only made detailed statistical comparisons of the DSC performance of H. pratti in the free flight and moving pendulum paradigms.…”
Section: Real-time Playback Paradigmmentioning
confidence: 99%